Textos fonéticos de Cuba (1965-2006). - Fernández de Castro, Félix (El Colegio de México, 2021)
In dialectology, geographical linguistics and sociolinguistics, phonetic transcription is often used to illustrate the speech analyzed in monographs, linguistic atlases and variation studies. This paper analyses nine such studies of the Spanish spoken in Cuba, all of them published between 1965 and 2006. It describes the work in which each phonetic text is included (with a sample of the transcription), its the-oretical framework and the system of phonetic notation employed by each author.